2021
DOI: 10.1111/ijcp.14218
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum thyroglobulin alteration after ultrasonography‐guided fine‐needle biopsy of suspicious cervical lymph nodes in the diagnosis of metastasis in patients with differentiated thyroid cancer

Abstract: Background: It is known that serum thyroglobulin (TG) can increase after fine-needle biopsy of thyroid nodules. We aimed to determine whether TG is increased after ultrasonography (US)-guided fine needle capillary biopsy (FNC) of suspicious cervical lymph nodes (LNs) in thyroidectomised patients and investigate the possible association between change in TG and cytology results.Material and Methods: Data of 188 patients who underwent FNC of suspicious cervical LNs were retrospectively evaluated. Demographical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The five-year survival rate of patients with well-differentiated tumors is significantly higher than that of patients with moderately and poorly differentiated tumors [22]. We herein found that the degree of differentiation of the missed diagnosis group was high, and a high degree of differentiation was an independent risk factor for the missed diagnosis of lymph node metastasis by MSCT, which may be attributed to the weak diffusion of well-differentiated tumor tissues [23] and inconspicuous lymph node metastasis. In addition, we also found that the negative expression of Ki-67 was closely related to the missed diagnosis by MSCT, as an independent risk factor.…”
Section: Discussionmentioning
confidence: 61%
“…The five-year survival rate of patients with well-differentiated tumors is significantly higher than that of patients with moderately and poorly differentiated tumors [22]. We herein found that the degree of differentiation of the missed diagnosis group was high, and a high degree of differentiation was an independent risk factor for the missed diagnosis of lymph node metastasis by MSCT, which may be attributed to the weak diffusion of well-differentiated tumor tissues [23] and inconspicuous lymph node metastasis. In addition, we also found that the negative expression of Ki-67 was closely related to the missed diagnosis by MSCT, as an independent risk factor.…”
Section: Discussionmentioning
confidence: 61%